USA, Firmaet og kommunisterne - Hansen, Peer Henrik (Arbejderhistorie - tidsskrift for historie, kultur og politik, 2012)
Peer Henrik Hansen: CIA, the Firm and the Communists, Arbejderhistorie 1/2012, s. 1-13. Even before the creation of the Central Intelligence Agency in 1947, the US and Danish intelligence communities were tied together through an agreement made in 1946 where the national services obligated each other to cooperate in working against Soviet and Eastern European targets, fighting communism, prepare a Stay behind network and develop the signals intelligence capacity towards he new enemy. The plan was to create a secret organization. In March 1948 Denmark experienced the so-called Easter Crisis. Norway, Sweden, the USA and other Western European countries experienced a similar crisis where it was feared that the communist coup in Czechoslovakia would spread to Western Europe. In a situation with rumors of an imminent Soviet invasion it was crucial to have the best relations with other intelligence services that in any way could provide useful information. After the March Crisis the Americans and the Danes finally found common ground for creating the planned organization, later known as the Firm. New evidence show that the operational leader of the Firm, Arne Sejr, was in fact employed by the Danish military intelligence service and not, as presumed for years, working privately and somewhat independently.